Highly purified CNTs: an exceedingly efficient catalyst support for PEM fuel cell. Issue 38 (31st March 2016) - Gupta, Chanchal; Maheshwari, Priyanka H.; Sachdev, Divya; Sahu, A. K.; Dhakate, S. R.
Abstract : High performance in PEM fuel cells has been achieved using purified CNTs as catalyst support. Abstract : High performance in PEM fuel cells has been achieved using purified CNTs as catalyst support. Pt/CNT nanocomposites were synthesized by reducing Pt salt on CNTs in the presence of ethylene glycol as solvent and in inert atmosphere. The reactions were carried out using both pristine and purified MWCNTs under different pH and atmospheric conditions. The detailed physical and electrochemical characterization revealed that a highly active catalytic surface could be achieved on reducing Pt on defect-free, purified MWCNTs. A further elaborated mechanism is discussed, which illustrates that reduced Pt nanoparticles form a chelate in the presence of nitrogen at neutral pH. This results in increased stability and enhanced catalytic activity. The I – V performance of a unit PEM fuel cell using the synthesized catalyst (with purified CNTs as catalyst support) showed a peak power density of 818 mW cm −2 . The performance repeated in triplicate was found to be consistent and exceptionally high (>80%) in comparison with 448 mW cm −2, the value obtained while employing pristine CNTs as support and tested under similar conditions. Moreover, a novel experimental support was given to confirm the number of electrons involved in the oxygen reduction reaction (ORR) on these highly purified CNT supported catalysts.